2017
DOI: 10.1080/13561820.2016.1249280
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of a multifaceted intervention to promote “speaking up” and strengthen interprofessional teamwork climate perceptions

Abstract: Communication failure is a leading cause of error and is often due to inhibition of individuals to speak up in interprofessional healthcare environments. The present study sought to evaluate the impact of a multifaceted intervention designed to promote speaking up on teamwork climate in one clinical department of a large community hospital based in Canada. The multifaceted intervention included a role-playing simulation workshop, teamwork climate data feedback and facilitated discussion with the interprofessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 57 publications
0
49
0
2
Order By: Relevance
“…Ginsburg and Bain [38] used simulation as part of their multifaceted intervention to promote speaking up behaviour and teamwork in an emergency department (ED). This intervention took place within the context of the hospital's new Accountability Framework, which holds staff accountable to speak up in the face of unsafe or unprofessional behaviour.…”
Section: Educational Interventions and Simulation Exercisesmentioning
confidence: 99%
See 4 more Smart Citations
“…Ginsburg and Bain [38] used simulation as part of their multifaceted intervention to promote speaking up behaviour and teamwork in an emergency department (ED). This intervention took place within the context of the hospital's new Accountability Framework, which holds staff accountable to speak up in the face of unsafe or unprofessional behaviour.…”
Section: Educational Interventions and Simulation Exercisesmentioning
confidence: 99%
“…2, mixed results were found for the impact of the interventions on outcomes related to psychological safety, speaking up and voice. Five studies [38,39,41,43,44] reported improved and three studies [35,40,43] found mixed results for "questioning, challenging, reporting or speaking up". One further study [36] found no significant relationship.…”
Section: Interventions Most Effective At Improving Psychological Safementioning
confidence: 99%
See 3 more Smart Citations